2002
DOI: 10.1079/bjn2002580
|View full text |Cite
|
Sign up to set email alerts
|

Dietaryn-3 andn-6 fatty acids alter avian metabolism: metabolism and abdominal fat deposition

Abstract: The effects of dietary saturated fatty acids and polyunsaturated fatty acids (PUFA) of the n-3 and n-6 series on weight gain, body composition and substrate oxidation were investigated in broiler chickens. At 3 weeks of age three groups of chickens (n 30; ten birds per group) were fed the fat-enriched experimental diets for 5 weeks. These diets were isonitrogenous, isoenergetic and contained 208 g protein/kg and 80 g edible tallow, fish oil or sunflower oil/kg; the dietary fatty acid profiles were thus dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
6
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 36 publications
9
90
6
6
Order By: Relevance
“…Contrary to our results, it have been reported that diets rich in MUFA (Kris-Etherton et al 1999) and PUFA (Newman et al 2002) such canola oil is, decreased plasma cholesterol in birds and human. Also, Crespo and EsteveGarcia (2002) working with female broiler fed different types of fat (10% fat, olive oil, sunflower and linseed) determined that cholesterol in legs was lower in diets containing sunflower or linseed oil (high in PUFA) than in diets containing fat (SFA) or olive oil (high in MUFA), due to the increase in lipid oxidation by an increased endogenous lipogenesis.…”
Section: Results and Discusioncontrasting
confidence: 56%
“…Contrary to our results, it have been reported that diets rich in MUFA (Kris-Etherton et al 1999) and PUFA (Newman et al 2002) such canola oil is, decreased plasma cholesterol in birds and human. Also, Crespo and EsteveGarcia (2002) working with female broiler fed different types of fat (10% fat, olive oil, sunflower and linseed) determined that cholesterol in legs was lower in diets containing sunflower or linseed oil (high in PUFA) than in diets containing fat (SFA) or olive oil (high in MUFA), due to the increase in lipid oxidation by an increased endogenous lipogenesis.…”
Section: Results and Discusioncontrasting
confidence: 56%
“…Meat, milk and egg play an important role in human nutrition (Newman et al 2002;Basmacıoglu et al 2003). Consumers are increasingly interested in functional foods that can prevent or ameliorate disease (Patterson et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, such information would provide a useful basis for making inferences on the partitioning and overall efficiency of LC n-3 PUFA utilisation in the broiler. It is known that certain tissues, such as brain, have an innate requirement or preference for DHA for healthy functioning (37) (87) . Initial findings of recent studies have established that the proportions of DHA in breast muscle, leg muscle, brain, heart, kidneys, liver, skin (with subcutaneous fat) and abdominal fat increase in response to increasing dietary DHA content and that the tissue DHA content is higher in birds fed diets containing 4 mg DHA/kg feed than in controls (86) .…”
Section: Efficiency Of Accumulation Of Long-chain N-3 Pufa In Differementioning
confidence: 99%
“…Adding relatively high concentrations of vitamin E to poultry diets also prevents much of the oxidative deterioration associated with increasing the n-3 PUFA content of the meat (89)(90)(91)98,99) . The recommended dietary vitamin E concentration for finishing broilers (birds in the final phase of growth before slaughter, when nutrition is often adjusted to reflect these changes) is 50 mg/kg (100) but typical levels of inclusion of vitamin E (as a-tocopheryl acetate) with n-3 PUFA-enriched diets are £300 mg/kg (84,85,87,(94)(95)(96)(97)(98)101,102) . A relationship has been proposed to predict the dietary vitamin E content required for a particular dietary PUFA content in order to maintain the oxidative stability of meat (103) .…”
Section: Quality Of Enriched Poultry Meatmentioning
confidence: 99%